Analisis Kinerja Keuangan Berdasarkan Rasio Likuiditas Dan Rasio Profitabilitas Pada PT. Unilever Indonesia Tbk. - Gafthari Rumindan; Agustinus Mantong; Grace Sriati Mengga (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
This research aims to analyze the financial performance of PT. Unilever Indonesia Tbk which is listed on the Indonesia Stock Exchange, based on the Liquidity Ratio and Profitability Ratio at PT. Unilever Indonesia Tbk for the 2020-2022 period. Data Analysis Technique is a quantitative analysis technique, namely data in the form of numbers which include financial reports at PT. Unilever Indonesia Tbk. In the research results based on Liquidity and Profitability Ratios, the financial performance of PT. Unilever Indonesia Tbk's Liquidity Ratio experienced fluctuations from 2020-2022 or instability in PT's financial performance. Unilever Indonesia Tbk. The Liquidity Ratio can be said to be in poor condition with the Current Ratio and Quick Ratio methods not meeting industry standards, while the Cash Ratio is able to reach industry standards that have been set. Then the Profitability Ratio can be said to be in poor condition, with the Return On Equity method meeting industry standards, while Return On Investment and Net Profit Margin do not meet industry standards because they decline every year.